Pengaruh Kualitas Layanan Mobile Banking BCA Terhadap Kepuasan Pelanggan E-Commerce - Davina Evangeline; Filani Zikri Hassan; Edy Safni Rosa (LPPM IBI Kesatuan, 2021)
The purpose of this research is to determine the influence of service quality Mobile Banking BCA towards E-commerce customer satisfaction specifically Shopee customers in Bogor. There were several previous researches had been done with different periods, samples, and methods with the various results so it is necessary to do further research. Additionally, the researcher also has interest to do further research since E-commerce business has been rapidly growing and how it is impacted the products of banking sector which is Mobile Banking BCA. This research consists of four independent variable taken out from service quality dimensions which are efficiency, fulfillment, reliability and privacy and one dependent variable which is e-commerce customer satisfaction. Primary data were collected by using questionnaire from costumers shopee in Bogor. At the first, the researcher uses validity and reliability test for questionnaire. Furthermore, the researcher tested the classical assumptions using the multiple linear regression with the margin of error 5 %. Last the researcher tests the hypothesis using t-test, f-test and coefficient of determination. The result indicates that reliability has no partial significant influence toward e-commerce customer satisfaction while efficiency, fulfillment and privacy have partially significant influence toward e-commerce customer satisfaction. Moreover, those four independent variables have simultaneously significant to the dependent variable which is 77,3%. Keywords: Service Quality, Efficiency, Reliability, Fulfillment, Privacy, E-commerce Customer Satisfaction